1959
DOI: 10.1002/jsfa.2740100604
|View full text |Cite
|
Sign up to set email alerts
|

The comprehensive analysis of grasses

Abstract: An attempt has been made to account quantitatively for the main groups of chemical compounds in the dry matter of grasses. This was done by successive extractions with ethanol‐benzene, warm water and ammonium oxalate solution, followed by digestion with pepsin and a delignifying treatment to isolate a holocellulose fraction. The polysaccharides in the holocellulose were determined. It was found possible to account for 97–98% of the grass dry matter and to identify all but 1–3% of it. The use to which such deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1959
1959
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…An early in vitro study also revealed that a considerable proportion of the pectin in alfalfa was digested by mixed cultures (Dehority et al ., ). Similar to previous results (Waite & Gorrod, ; Mertens, ; Mullen et al ., ), the yields of chemical‐extracted pectin were 2.8%, 3.7%, and 9.3% for CS, CW, and AH, respectively, indicating a consistently higher pectin content in AH than that in CS or CW when the same extraction conditions are used.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…An early in vitro study also revealed that a considerable proportion of the pectin in alfalfa was digested by mixed cultures (Dehority et al ., ). Similar to previous results (Waite & Gorrod, ; Mertens, ; Mullen et al ., ), the yields of chemical‐extracted pectin were 2.8%, 3.7%, and 9.3% for CS, CW, and AH, respectively, indicating a consistently higher pectin content in AH than that in CS or CW when the same extraction conditions are used.…”
Section: Resultssupporting
confidence: 93%
“…An early in vitro study also revealed that a considerable proportion of the pectin in alfalfa was digested by mixed cultures (Dehority et al, 1962). Similar to previous results (Waite & Gorrod, 1959;Mertens, 2002;Mullen et al, 2010), the yields of chemical-extracted pectin were 2.8%, 3.7%, and 9.3% for CS, CW, and AH, respectively, indicating a consistently higher pectin content in AH than that in CS or CW when the same extraction conditions are used. Our in vitro fermentation experiment was first conducted to validate the practicability of the designed primers for monitoring the abundance of T. saccharophilum under different pectin contents derived from pure pectin and forages.…”
Section: Validation Of the Specificity And Sensitivity Of The Designesupporting
confidence: 84%
“…Agronomy 2019, 9, x FOR PEER REVIEW 2 of 11 Analytical procedures to quantify the chemical composition of forages have been long established [18,19] and the influence of drying methods on forage sample constituents is well documented. For example, greater drying temperatures lead to caramelization of sugars [20], Maillard products [21] or a reduced recovery of soluble sugars [22], whereas reported changes in CP level are inconsistent [23,24].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies in this laboratory have investigated the digestion of cellulose and hemicellulose from intact forages by pure cultures of rumen bacteria (9,17). The only other carbohydrate occurring in appreciable quantities in forage is pectin, which can constitute from 10 to 20% of the total carbohydrate complex in grasses and alfalfa, respectively (22,25). Thus, the present study was undertaken to investigate the ability of several species of rumen bacteria to ferment both isolated and naturally occurring pectins.…”
mentioning
confidence: 99%